Interaction and Interactivity Process: Communication in Digital Education - Andreia de Bem Machado; Francisco Fialho (JINAV: Journal of Information and Visualization, 2020)
Communication between subjects is a challenge that is present in the different dimensions of society. In the educational context it is permeated by different technologies. With the pandemic of COVID-19, technological tools have been extended to several ways of learning, which was present in face-to-face teaching through non-face-to-face classes and also in distance education. Thus, new challenges in communicability between students, teachers and knowledge were present in this scenario. This research intends to share the experiences lived in the educational universe in the distance modality and also in the classes in non-presential regime.